ANALISIS HASIL BELAJAR SISWA MTs KELAS VII PERSAMAAN LINEAR SATU VARIABEL BERBANTUAN SCRATCH - Ahmad Hasya Al Hafizh; Masta Hutajulu (LPPM Universitas Advent Indonesia, 2023)
To improve student learning results, changes are needed in the learning process in a better path. The purpose of this study was to analyze student learning result about one-variable linear equations with CTL before and after the application of scratch-based media. This type of research is a class action research with 2 cycles in which the subjects are 30 students of class VII in one MTs Kota Cimahi. Data obtained through observation and tests at the end of each cycle. In cycle 1 students carry out teaching and learning activities with Student Worksheets and at the end of cycle 1 a test is carried out to find out student learning result during cycle 1. The data is analyzed and then used as a reference for the implementation of cycle 2 which in practice, students study with Student Worksheets plus the existence of media-based assistance scratch application. After cycle 2 ends, students are given another test with the same indicators as cycle 1. In the test results from cycle 1, out of 30 students, only 3 students get learning outcomes in the high category, while the test results for cycle 2, out of 30 students, only 1 student who get the value of learning outcomes in the high category. The results of this study indicate that the application of contextual learning with the help of scratch-based media applications has not been able to improve mathematics learning outcomes in the material of one-variable linear equations.